Application of remote sensing and GIS for dengue epidemic surveillance in Petaling Jaya, Malaysia - Ahmad Zahawir, Mior Mohd Hadafi (2008)
Remote sensing and GIS data was used in dengue epidemic mapping. The work focused on three main applications. First, mapping the dengue epidemic incident location by analysing the cases which have relationship between one another, like cases occurring in 200 meter range from the first case and time period in one to two weeks. Secondly, application for land use,where land use information was extracted from high resolution satellite image,Ikonos. Dengue cases occurred in any land use will be observed where the epidemic was influenced by land use factors. Thirdly, the dengue cases occurred will be observed whether it was influenced by climate factors such as rainfall and temperature, including temperature and vegetation indices, obtained from medium resolution satellite images. These data was then analysed using statistical method. Although the results can show the spot area of dengue cases occurrence, the dengue cases risk index in area based on land use and other factor in that area will also be shown. Results from statistical analysis will show the model development and verification, whether it can be accepted or not. The main conclusion of this work will show the levels of remote sensing and GIS technology used, which can help in dengue epidemic monitoring in Malaysia.